Is internal migration bad for receiving urban centres? Evidence from Brazil, 1995-2000 - Céline Ferré (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
During the twentieth century, internal migration and urbanization shaped Brazil's economic and social landscape. Cities grew tremendously, while immigration participated in the rapid urbanization process and the redistribution of poverty between rural and urban areas. In 1950, about a third of Brazil's population lived in cities; this figure grew to approximately 80 per cent by the end of the nineteenth century. The Brazilian population redistributed unevenly - some dynamic regions became population magnets, and some neighbourhoods within cities became gateway clusters in which the effects of immigration proved particularly salient. This study asks, has domestic migration to cities been part of a healthy process of economic transition and mobility for the country and its households? Or has it been a perverse trap?
Keywords: R2; O54; N96; 330; urbanization; migration; mobility; poverty; households; Brazil